2007
DOI: 10.1074/jbc.m705859200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Integrated Stress Response Regulates Lovastatin-induced Apoptosis

Abstract: Lovastatin, a potent inhibitor of mevalonate synthesis, can readily induce apoptosis in a subset of human tumor types including head and neck squamous cell carcinomas (HNSCC). We recently identified activation of transcription factor (ATF) 4 as a lovastatin induced gene in HNSCC cells. ATF4 plays a significant role in regulating cellular responses to a wide variety of stress inducers known as the integrated stress response (ISR). These cell stresses lead to the phosphorylation of eukaryotic initiation factor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 45 publications
1
48
0
Order By: Relevance
“…We next performed quantitative reverse transcriptase PCR analysis to compare the expression profile of (activation of transcription factor) ATF3 and GAPDH (Figure 3b) mRNA in monosome-and polysome-enriched fractions. It has been shown before that increased ATF3 expression is an indication of attenuation of protein translation during stress (Niknejad et al, 2007). We found that ATF3 mRNA (Figure 3b) shifted toward the heavier polysome fractions in lovastatin-treated cells.…”
Section: Lovastatin Treatment Inhibits Global Protein Translationsupporting
confidence: 60%
See 1 more Smart Citation
“…We next performed quantitative reverse transcriptase PCR analysis to compare the expression profile of (activation of transcription factor) ATF3 and GAPDH (Figure 3b) mRNA in monosome-and polysome-enriched fractions. It has been shown before that increased ATF3 expression is an indication of attenuation of protein translation during stress (Niknejad et al, 2007). We found that ATF3 mRNA (Figure 3b) shifted toward the heavier polysome fractions in lovastatin-treated cells.…”
Section: Lovastatin Treatment Inhibits Global Protein Translationsupporting
confidence: 60%
“…Using EGFR-targeting agents requires combination-based therapies to enhance their clinical activity. Our recent studies have shown that the depletion of mevalonate metabolites affects the activity of a number of cell signaling cascades, including inhibitory effects on EGFR activity and their downstream signaling pathways (Mantha et al, 2005;Niknejad et al, 2007). Combinations of statins with agents targeting EGFR activity, such as gefitinib, induce a potent synergistic cytotoxic response in a variety of responsive tumor types, including SCC (Mantha et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, levels of other mevalonate metabolites may also be perturbed in PEX2 Ϫ/Ϫ mice leading to an activation of PERK and/or GCN2. For instance, inhibition of cholesterol biosynthesis can trigger the ISR, probably because of alterations of membrane cholesterol composition (56,57). Perturbations of non-sterol isoprenoids downstream of the farnesyl pyrophosphate branch point also contribute to the development of ER stress.…”
Section: Er Stress and Activation Of Srebp-2 Genes Independent Of Chomentioning
confidence: 99%
“…The synergistic effects of lovastatin in combination with EGFR-TKIs that we previously reported were due to its ability to inhibit EGFR activity (30) and to induce the integrated stress response; particularly, the ATF3 that regulates the apoptosis induction of this pathway (35,36). We first evaluated the effect of monensin treatment alone and in combination with erlotinib on ligand-induced EGFR activation and its downstream signaling pathways by Western blot analysis.…”
Section: Monensin Enhances the Erlotinib Inhibition Of Egfr Activationmentioning
confidence: 99%